2015
DOI: 10.1039/c5cp06165b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the coordination behavior of formate and formamidoximate with dioxovanadium(v) cation: implications for selectivity towards uranyl

Abstract: Poly(acrylamidoxime)-based fibers bearing random mixtures of carboxylate and amidoxime groups are the most widely utilized materials for extracting uranium from seawater. However, the competition between uranyl (UO2(2+)) and vanadium ions poses a significant challenge to the industrial mining of uranium from seawater using the current generation of adsorbents. To design more selective adsorbents, a detailed understanding of how major competing ions interact with carboxylate and amidoxime ligands is required. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 57 publications
(69 reference statements)
2
33
0
Order By: Relevance
“…A similar E 0 is identified in the V(V) metal oxide standard, Na 3 VO 4 , particularly when compared to V(IV) and V(III) species. Although anticipated from the literature 32 and previous computational work 33 35 , this is the first instance the + 5 oxidation state is experimentally confirmed for adsorbent-bound V.…”
Section: Resultsmentioning
confidence: 47%
“…A similar E 0 is identified in the V(V) metal oxide standard, Na 3 VO 4 , particularly when compared to V(IV) and V(III) species. Although anticipated from the literature 32 and previous computational work 33 35 , this is the first instance the + 5 oxidation state is experimentally confirmed for adsorbent-bound V.…”
Section: Resultsmentioning
confidence: 47%
“…Previous computational evaluations of AO-uranyl complexes have largely focused on mononuclear structures with binding modes in Figure 1A-C. In contrast, evaluations of zwitterionic AO species are limited to a few computational papers evaluating AO tautomerization on uranium 53 and vanadium 54,55 binding as well as energetics of AO tautomerization. 56,57 Together these studies suggest AO tautomerization, before or after complexation, influences the binding mode and selectivity of AO based materials.…”
Section: Aao-hmentioning
confidence: 99%
“…Although a number of recent studies have shed important light on speciation of uranyl in different aqueous environments, [13][14][15][16] [17] little is known about speciation of vanadium species in seawater [12,[18][19][20][21]. Equilibrium complexation of HVO4 2has been previously determined from speciation calculations using free ion concentrations modeled for seawater and calculated stability contestants at the appropriate ionic strength [20].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the aqueous environment induced a conformational change on the two VOH moieties from C2 symmetry to Cs symmetry and an exchange of water molecules between the first solvation sphere of H2VO4and the solution. Recent work with coupled cluster theory examined coordination number and prominent binding modes of water and other ligands to vanadyl (VO2 + ) [19]. From a single-crystal structure, Rao and coworkers have found a unique binding mode of vanadium to amidoxime-type ligand, where the V-O bonds are sequentially displaced by two amidoximate oxygens [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation